2005
DOI: 10.1111/j.1365-3059.2005.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

First report of Tomato leaf curl New Delhi virus infecting bitter gourd in Pakistan

Abstract: Bitter gourd ( Momordica charantia ; family Cucurbitaceae) is a vegetable cultivated in many areas of Pakistan. Plants showing yellow blotch symptoms were observed in several fields in the vicinity of Lahore, Pakistan, with an average incidence of 60 -70%. Leaf samples were collected from four diseased and from two apparently healthy (symptomless) plants, and used for DNA extraction.The presence of a begomovirus was confirmed by PCR amplification using a degenerate primer pair designed to conserved regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Squash leaf curl virus (SLCV) found in the southwestern desert of the USA (Cohen et al 1983) was the first recorded cucurbit-infecting begomovirus. Subsequently, cucurbit-infecting begomoviruses have become a serious problem in tropical and subtropical areas, including Watermelon chlorotic stunt virus (WmCSV) in Yemen (Jones et al 1987), Cucurbit leaf curl virus (CuLCuV) in western USA and northern Mexico (Brown et al 2000), Melon chlorotic leaf curl virus-Guatemala (MCLCuV-GT) in Central America (Brown et al 2001), Squash leaf curl Philippines virus (SLCPHV) and Luffa yellow mosaic virus (LYMV) in Philippines and Vietnam (Revill et al 2003), Squash leaf curl China virus (SLCCNV) and Squash leaf curl Yunnan virus (SLCYNV) in China (Hong et al 1995;Xie and Zhou 2003), SLCPHV in Taiwan (Tsai et al 2007), and Tomato leaf curl New Delhi virus (ToLCNDV) in Thailand and Pakistan (Ito et al 2008;Tahir and Haider 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Squash leaf curl virus (SLCV) found in the southwestern desert of the USA (Cohen et al 1983) was the first recorded cucurbit-infecting begomovirus. Subsequently, cucurbit-infecting begomoviruses have become a serious problem in tropical and subtropical areas, including Watermelon chlorotic stunt virus (WmCSV) in Yemen (Jones et al 1987), Cucurbit leaf curl virus (CuLCuV) in western USA and northern Mexico (Brown et al 2000), Melon chlorotic leaf curl virus-Guatemala (MCLCuV-GT) in Central America (Brown et al 2001), Squash leaf curl Philippines virus (SLCPHV) and Luffa yellow mosaic virus (LYMV) in Philippines and Vietnam (Revill et al 2003), Squash leaf curl China virus (SLCCNV) and Squash leaf curl Yunnan virus (SLCYNV) in China (Hong et al 1995;Xie and Zhou 2003), SLCPHV in Taiwan (Tsai et al 2007), and Tomato leaf curl New Delhi virus (ToLCNDV) in Thailand and Pakistan (Ito et al 2008;Tahir and Haider 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Although ToLCNDV was first discovered on tomato, it is also reported to cause extensive damage in cucurbitaceous plants. Several new disease reports revealed that ToLCNDV caused severe symptoms on bitter gourd (Tahir and Haider 2005), bottle gourd (Ito et al 2008), cantaloupe (Samretwanich et al 2000a), cucumber (Samretwanich et al 2000b), muskmelon (Samretwanich et al 2000d), watermelon (Mansoor et al 2000), and wax gourd (Samretwanich et al 2000c), in Thailand or Pakistan. Most ToLCNDV isolates were only transmitted by whiteflies naturally while only the potato isolate has been shown to be mechanically transmitted to its original host (Usharani et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…ToLCNDV is known to infect tomato in India since nearly two decades, but during the last one decade, its host range has increased enormously to various crops such as potato [21], papaya [12], eggplant [11] okra [23] and several cucurbitaceous vegetables like bottle gourd, bitter gourd, cucumber, ivy gourd, long melon, pumpkin, ridge gourd and watermelon in northern India and chayote in north-western India [7,16,17,20]. In Pakistan, besides tomato, ToLCNDV was also reported on crops like chilli [5], bitter gourd [18], and on weed Eclipta prostrata [3]. In Thailand, ToLCNDV has been reported to infect bottle gourd, cucumber and muskmelon [6].…”
mentioning
confidence: 99%
“…Similarly, Tomato leaf curl New Delhi virus (ToLCNDV) was first time recorded in north India in 1995 (Srivastava et al, 1995) and subsequently reported across the country (Khan et al, 2006;Padidam et al, 1995;Raj et al, 2005;Sohrab et al, 2003;Usharani et al, 2004). Later on, the virus has been reported from other neighboring countries like Pakistan (Haider et al, 2006;Hussain et al, 2004;Hussain et al, 2005;Mansoor et al, 1997;Mansoor et al, 2000b;Tahir and Haider, 2005), Bangladesh (Maruthi et al, 2005), Thailand (Ito et al, 2008) and Indonesia (Mizutani et al, 2011) where it has great concern in the association of various commercial crop diseases.…”
Section: Effect Of Begomoviruses Movement On Disease Dynamicsmentioning
confidence: 99%